TENDONITIS: THE MAJOR CAUSE OF PAIN IN OSTEOARTHRITIS - Bokhari, Syed Zahid Hussain (Journal of Ayub Medical College Abbottabad, 2012)
Background: The conventional concept of osteoarthritis is that it occurs as an aging and degenerative process resulting in reduction of the surface cartilage, narrowing of the joint space and reduction of the synovial fluid. The objective of this study was to introduce the new technique of unmasking and treating the underlying problem confirming lesions outside the knee joint being the cause of pain in osteoarthritic knee joint. Methods: Clinical work making the base of this paper was carried out at Pain and Plegia Centre, Dabgari Gardens Peshawar from 2005 to 2012. Patients reporting with knee pain were palpated deep around the knee joint and major tender spots identified upon Adductor tubercle on medial aspect and Gastrocnemius (lateral head) on lateral aspect proximal to the knee. These lesions were injected each with 20 mg of Triamcinolone Acetonide diluted in 2 ml of Xylocaine 2%. Results: The lesions responded favourably to the simple treatment and patients of pain knee joint of various durations were completely pain free. The optimum healing time of the lesions was 10 days. Conclusion: Osteoarthritic changes inside the knee joint may not be the cause of painful knee, rather it can be a referred pain. Two lesions, Adductor tubercle on medical side and lateral head of Gastrocnemius on the lateral side proximal to the knee joint are identified to attribute to this pain. Keywords: Pain, Knee Joint, Osteoarthritis, Tendonitis